2-APB and CBD-Mediated Targeting of Charged Cytotoxic Compounds Into Tumor Cells Suggests the Involvement of TRPV2 Channels - Neumann-Raizel, Hagit; Shilo, Asaf; Lev, Shaya; Mogilevsky, Maxim; Katz, Ben; Shneor, David; Shaul, Yoav D.; Leffler, Andreas; Gabizon, Alberto; Karni, Rotem; Honigman, Alik; Binshtok, Alexander M. (Frontiers in Pharmacology, 2019)
Targeted delivery of therapeutic compounds to particular cell types such that they only affect the target cells is of great clinical importance since it can minimize undesired side effects. For example, typical chemotherapeutic treatments used in the treatment of neoplastic disorders are cytotoxic not only to cancer cells but also to most normal cells when exposed to a critical concentration of the compound. As such, many chemotherapeutics exhibit profound side effects, often prohibiting their effective use in the treatment of cancer. Here we describe a mean for facilitated delivery of a clinically used chemotherapy compound doxorubicin, into hepatocellular carcinoma cell line (BNL1 ME). We demonstrated that these cells express large pore, cation non-selective Transient Receptor Potential (TRP) channel V2. We utilized this channel to shuttle doxorubicin into BNL1 ME cells. We show that co-application of either Cannabidiol (CBD) or 2-APB, the activators of TRPV2 channels, together with doxorubicin lead to significantly higher accumulation of doxorubicin in BNL1 ME cells than in BNL1 ME cells that were exposed to doxorubicin alone. Moreover, we demonstrated that sub-effective doses of doxorubicin when co-applied with either 2-APB or CBD, lead to a significant decrease in the number of living BNL1 ME cell and BNL1 ME cell colonies in comparison to application of doxorubicin alone. Finally, we have demonstrated that the doxorubicin-mediated cell death effect was significantly more potent, requiring an order of magnitude lower dose, when co-applied with CBD than with 2-APB. We suggest that CBD may have a dual effect in promoting doxorubicin mediated cell death by facilitating the entry of doxorubicin via TRPV2 channels and preventing its clearance from the cells by inhibiting P-glycoprotein ATPase transporter. Collectively, these results provide a foundation for the use of large pore cation-non selective channels as “natural” drug delivery systems for targeting specific cell types.